Insulin resistance as a mediator of the association between obesity, high-intensity binge drinking, and liver enzyme abnormalities in young and middle-aged adults: a cross-sectional study - Jiayi Zhu; Jiayi Zhu; Jiayi Zhu; Yinglong Duan; Ying Li; Yi Zhou; Zitong Lu; Nandan Chen; Juan Luo; Xingxing Wang; Xiaoqian Dong; Andy S. K. Cheng; et al. (Frontiers in Nutrition)
BackgroundBinge drinking (BD) and obesity are well-established risk factors for liver enzyme abnormalities, but how varying intensities of BD interact with obesity to affect liver function remains unclear. This study aims to examine whether insulin resistance (IR) mediates the associations between different levels of BD, obesity, their interaction, and liver enzyme abnormalities.MethodsThis cross-sectional study included 137,878 young and middle-aged adults who underwent physical examinations in southern China between August 2017 and March 2024. BD was self-reported, and IR was assessed using the triglyceride–glucose (TyG) index. Causal mediation analysis within the counterfactual framework was used to quantify the mediating role of the TyG index in the associations involving BD intensity, obesity, their interaction, and liver enzyme abnormalities.ResultsThe interaction between obesity and high-intensity binge drinking (HIBD) was significantly associated with liver enzyme abnormalities (OR, 1.591; 95% CI, 1.401–1.806). IR, measured by the TyG index, statistically accounted for 36.6% (OR, 1.034; 95% CI, 1.029–1.039) of this association, exceeding the proportion explained in the HIBD alone (25.9%) or obesity alone (16.7%) pathways. No significant mediating effect of IR was observed for non-BD or low-intensity BD, regardless of obesity status.ConclusionThe TyG index serves as a critical mediator in the synergistic effects of HIBD and obesity on liver enzyme abnormalities. Targeting IR and reducing the intensity of alcohol consumption may help mitigate liver injury in young and middle-aged adults with obesity.